Integration of Game-Based Learning to Strengthen the Pedagogic Competence of Digital Literacy of PGSD Students in the Era of Digital Transformation: A Systematic Literature Review - Mirdan Kurniawan; Berta Apriza; Rohmani; Yasinta Mahendra; Bunga Adelia (Journal for Lesson and Learning Studies, 2025)
The paradigm shift in education due to digital transformation requires prospective elementary school teachers to have adequate digital pedagogical competencies in order to create relevant learning experiences. However, various findings show that teacher education programs are still limited in integrating innovative approaches, resulting in a gap between graduates' abilities and the needs of 21st-century learning practices. This study aims to critically analyze, evaluate the effectiveness, and synthesize various models and strategies for integrating Game-Based Learning (GBL) in strengthening the digital literacy pedagogical competencies of elementary school teacher education students. The method used is a Systematic Literature Review (SLR) with PRISMA guidelines, through a review of ten empirical articles published in the 2020–2024 period. The results of the analysis show that GBL and gamification can increase motivation, positive attitudes, and mastery of techno-pedagogical content knowledge (TPACK) among prospective teachers. Student involvement as game designers proved to be more effective than theory-based learning alone. The main obstacles to the implementation of GBL include limited resources, infrastructure, and training. The implications of this research emphasize the need for a shift in teacher education curricula towards more practical, participatory, and design-oriented learning models, while encouraging policymakers to strengthen institutional support for teacher competency development in the digital age.